POINTS OF VIEW OF A FOREIGN CONSUMER OF TOURIST SERVICES IN THE FIELD OF HOSPITALITY OF IVANO-FRANKIVSK REGION - Arkhypova, Liudmyla; Diachuk, Iryna (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
In the Ivano-Frankivsk region, in the conditions of unstable economic and political situation, there is a need for in-depth study of the prospects of inbound tourism. The lack of sufficient and thorough information about the social type and features of the modern foreign tourist determines the novelty of this work. According to a survey conducted among foreign tourists of Ivano-Frankivsk region, a social portrait of a foreign tourist was formed, which allows to determine the needs and expectations of foreign guests. An analysis of survey data by geographical, demographic, socio-economic and behavioral criteria was conducted. According to the analysis, the main aspects that express the needs and expectations of foreign visitors during the trip to Ivano-Frankivsk region. The main motivation for foreign tourists to travel to the Carpathians is the desire for entertainment and recreation. Bukovel Resort has become a leader among foreign tourists. The second place was taken by the regional center - the city of Ivano-Frankivsk with its tourist attractions: the fortress gallery "Bastion" and the festival "Stanislav Marmalade". A foreign tourist of Ivano-Frankivsk region is on average willing to spend 199.5 EUR per day, 368 EUR per person and 640.5 EUR for the entire trip. According to the survey, foreign tourists of Ivano-Frankivsk region prefer amateur tourism with complete or partial refusal of assistance from tour operators or travel agents. Quite a large number of tourists (20%) said that they rest alone. It is observed that traveling alone is more common for males. Half of the surveyed tourists (49%) preferred hotels when traveling, 18% of respondents chose private estates for recreation. Most foreign tourists choose food in restaurants (39%) and cafes (29%). A significant amount of additional costs foreign tourists spend on souvenirs (26% of respondents). 18% of respondents spend money on entrance tickets, and 12% - on master classes. It is determined that the focus should be on improving the infrastructural, informational, organizational and cultural and entertainment components of the tourist product offered to foreign visitors. Possible ways to improve the tourist services of Ivano-Frankivsk region based on the analysis are substantiated.